EFFECT OF DIGITAL CURRENCY ON FINANCIAL MARKETS: : Analysis of Private Banks in Kurdistan Region of Iraq - Rizhin Nuree Othman; Khowanas Saeed Qader; Sanarya Adnan Anwer; Hawkar Anwar Hamad; Hamin Khasrow Ibrahim; Bayar Gardi; Pshdar Abdalla Hamza; Dashty Ismil Jamil (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The influence that digital currency has had on the activities of platform companies are discussed in this article. Companies employ digital platforms to increase productivity, strengthen client relationships, and cut expenses. The study applied quantitative method by collected 116 questionnaires. Finally, the findings revealed that, demand side and the demand side the study focused on (Security, Usability, Irrevocability, Marketing and reputational effects) positively and significantly have influence on financial market. Moreover, it was found that the supply side had more influence than demand side on financial market.